HUBUNGAN MOTIVASI BELAJAR DAN KEMANDIRIAN BELAJAR SISWA DENGAN HASIL BELAJAR PADA MATA PELAJARAN SENI BUDAYA SISWA SMPN 35 KOTA PADANG - Drs. Suib Awrus, M.Pd., SAYUR MATUA, Dra. Lisa Wisdiarti, M.Sn., (Jurusan Seni Rupa FBS UNP Padang, 2017)
The results of the study found that there is a significant and positive correlation between motivation and the learning result of art and culture subjects of students of grade VIII SMPN 35 Kota Padang, There is a significant and positive correlation between the independence of learning and learning outcomes in the subject of art and culture of students SMPN 35 Kota Padang, There is a significant and positive correlation between motivation and independence together with learning outcomes in the subject of art and culture of students SMPN 35 Kota Padang.Kata Kunci: Motivasi, Kemandirian, Hasil Belajar.